Sosialisasi Lubang Biopori Dalam Pengelolaan Sampah Organik - Yulia; Effendi Nurzal; Manovri Yeni; Nafisah Hanim (JKA, 2024)
Biopores is a technique for water infiltration (water absorption) in surface areas of the land to restore soil fertility, protect the water system and reduce waterlogging/surface runoff in areas that lack water absorption. One of the organic wastes that can be filled into the biopore holes is coffee grounds. Coffee grounds are the coffee residue left after the brewing process or grinding the coffee beans. Often coffee grounds are considered useless waste and are simply thrown away. Through this International Community Service (PKM) activity, it is hoped that compost can be produced in the soil so that it can improve the quality of the soil (fertilize the soil). Apart from that, it can absorb surface water into the ground and reduce surface waterlogging. The biopore method was first discovered in 2008 by Dr. Kamir R Brata, a researcher from IPB (Bogor Agricultural Institute). Biopores are absorption holes made vertically into the ground to reduce waterlogging and increase water absorption. The conclusions that can be concluded from this Community Service activity are as follows: This activity has produced compost in the soil so that it can improve the quality of the soil. This activity has also succeeded in making water infiltration into the soil very well which can reduce standing water on the surface of the soil.